Nanomaterials for biomedical applications: Addressing regulatory hurdles and strategic solutions - Sunil Gujjar; Samiksha Kukal; Prakash Jayabal; Neha Balaji; Saloni Sainger; Srabaita Roy; Suneel Rallapalli; Ravikiran Mahadevappa; Shilpi Minocha; Saran Kumar; Santosh Mathapati (Nano Trends, 2025)
Nanotechnology has revolutionized modern healthcare by providing innovative solutions for the diagnosis, treatment, and monitoring of various medical conditions. The unique biological, chemical, and mechanical attributes of nanomaterials have favoured their use for various medical applications, including drug delivery, tissue engineering, implantable devices, bio-molecular detection, and diagnostics. However, potential risks associated with nanomaterial usage on health and environment raised concerns regarding their safety and regulatory oversight. Focusing exclusively on nanomaterial design with less attention towards nano-bio interaction has become a significant bottleneck to their clinical translation. This review aims to provide a concise overview of the characteristics of nanomaterials which find exciting applications in biological and biomedical fields. More importantly, we put forth the current regulation status of these advanced materials, highlighting the potential challenges and uncertainties in the regulatory assessment, and discussing potential strategies for effective regulation. A robust regulatory framework will allow a smooth clinical translation of such materials without compromising patient safety.